A Matter of Trust: The Role of Communities in Energy Decision-Making, Case Study: Wuskwatim Hydroelectric Facility, Nisichawayasihk Cree Nation, Manitoba - Sajid, Shafak (Université d'Ottawa | University of Ottawa, 2016)
The case study focuses on Manitoba Hydro and Nisichawayasihk Cree Nation’s (NCN) Wuskwatim project. Project overview The Wuskwatim project was the first time a utility company and an Aboriginal community entered a partnership to develop a major generating station, where NCN would purchase 33 percent of the project’s shares. Primary Wuskwatim components include the 200 MW generating station and dam on the Burntwood River at Taskinigup Falls, transmission lines to the provincial power grid and an access road. Construction of the generating station ran from 2006 to late 2012 at a cost of $1.3 billion. The $300-million transmission line was a separate Manitoba Hydro project. Canada has been engaged in a diverse renegotiation of our energy systems. In this time of rapid change, it is challenging to isolate specific factors that affect community confidence. A dominant theme in this case study was the importance of building and maintaining relationships. There was time and effort spent on transforming the relationship between NCN and Manitoba Hydro to overcome the legacy of distrust between the two players. The Wuskwatim case demonstrates a shift from engagement to consultation to collaboration. The partnership and co-creation model should be based on shared long-term interests and positions Indigenous communities to be key players, decision-makers and beneficiaries of energy projects.
Keywords: Energy Projects; Indigenous communities; Social acceptance; Indigenous rights; Energy policy; Energy regulation; Electricity